The Correlation of Peer Social Support with Anxiety Levels of Students Working on Undergraduate Thesis at The Faculty of Nursing, University of Jember - Erti Ikhtiarini Dewi; Enggal Hadi Kurniyawan; Feno Aureola Maharani (Nursing and Health Sciences Journal (NHSJ), 2022)
One of the graduation requirements for students in obtaining a bachelor's degree is that making a scientific work which is called as thesis. In the process of writing a thesis, students often find various difficulties that can lead to negative feelings which if it is allowed to continue, it will cause psychological problems. This study analyzes the relationship between peer social support and anxiety levels of students who are writing thesis at the Faculty of Nursing, University of Jember. Furthermore, this study used an analytical correlational research design with a cross sectional approach. Meanwhile, respondents in this study were 113 college students who were writing thesis which were obtained by stratified random sampling technique. This study used a peer social support questionnaire and a State-Trait Anxiety Inventory (STAI) anxiety level questionnaire which were conducted online via google form. In addition, bivariate analysis was conducted by using the Kendall tau correlation test (p=0.05). The results show that 51 students (45.1%) have very high peer social support while 38 students (33.6%) have mild anxiety. Furthermore, there is no significant relationship between peer social support and anxiety levels (p<0.05) with a correlation coefficient of 0.189. The most influential factors in the anxiety level of college students who are writing thesis are fear and nervousness. For further researchers, it is expected that they can identify the factors which cause anxiety in college students who are writing thesis and provide interventions in the form of nursing actions.